Chromium-free Dacromet coating and use method thereof

By adding diazoles and amine derivatives to chromium-free dacrole coatings, stable chemical bonds are formed, and the problem of insufficient coating hardness and wear resistance is solved, which significantly improves hardness and maintains the stability and appearance of the coating. , suitable for surface protection of a variety of materials, reducing environmental and human body hazards.

CN119242097APending Publication Date: 2025-01-03重庆置道科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411466210.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The hardness and wear resistance of chromium-free dacro coatings are insufficient, especially in high salt spray and humid environments, and the addition of enhanced phases may lead to increased coating roughness and affect appearance.

Method used

In the chromium-free dacrocoal coating, diazole substances and amine derivatives are added as additives, and 2-o-chlorophenyl-4,5-diphenylimidazole and N-(tert-butoxycarbonyl)ethanolamine are used to form Stable chemical bonds to improve coating hardness.

Benefits of technology

It significantly improves the hardness of the chromium-free dacrole coating, avoids the use of heavy metal chromium, reduces potential harm to the environment and human health, maintains the stability and appearance of the coating, and is suitable for surface protection of a variety of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242097A_ABST
    Figure CN119242097A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of coating surface treatment, and discloses a chromium-free Dacromet coating, which comprises an additive, and the additive comprises a diazole substance and an amine derivative. The diazole substance is 2-o-chlorophenyl-4, 5-diphenyl imidazole, and the amine derivative is N-(t-butyloxycarboryl) ethanolamine. The mass ratio of the 2-o-chlorophenyl-4, 5-diphenylimidazole in the additive is 30 to 50g / L, and the mass ratio of the N-(t-butyloxycarbonyl) ethanolamine in the additive is 15 to 25g / L. The use concentration of the 2-o-chlorophenyl-4, 5-diphenylimidazole in the chromium-free Dacromet coating is 3 to 5g / L; and the use concentration of the N-(t-butyloxycarbonyl) ethanolamine in the chromium-free Dacromet coating is 1.5 to 2.5 g / L. The additive is added into the chromium-free Dacromet coating, so that the hardness of the coating can be improved on the basis of not changing the original coating performance and coating stability. And the coating does not contain heavy metal chromium, so that the performance is improved, and meanwhile, the effect of protecting the environment is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coating surface treatment and relates to a chromium-free Dacromet coating and a use method thereof. Background Art

[0002] Dacromet technology is a surface protection technology that is widely used for its excellent properties such as being pollution-free, pollution-free, free of hydrogen embrittlement, highly heat-resistant, and highly corrosion-resistant. Dacromet coatings have advantages in the surface protection of various materials such as steel, cast iron, aluminum and its alloys, and iron-based powder metallurgy. However, due to the problem of Cr pollution in the production and coating process of Dacromet coatings, the "chromium-free Dacromet" technology came into being. At present, the corrosion resistance of zinc-chromium coating (Dacromet) is better than that of zinc-aluminum coating, and the production cost is lower than that of zinc-aluminum coating, but the hardness and wear resistance of chromium-free Dacromet coating are relatively low, and it is not suitable for workpieces that require wear resistance.

[0003] Although chromium-free Dacromet coatings have solved the Cr pollution problem to a certain extent, their hardness and wear resistance are still insufficient. During transportation, assembly and use, workpieces are easily scratched and affected by scratches, which affects the appearance of the product. At the same time, in high salt spray and humid environments, the corrosion resistance of the coating is also weakened and needs to be further improved.

[0004] Some studies have shown that the hardness and corrosion resistance of chrome-free Dacromet coatings can be improved by adding reinforcing phases to them. However, this method has some drawbacks, such as excessive addition of reinforcing phases may increase the roughness of the coating and affect the appearance of the product. Therefore, further research and improvement of this method is needed to improve the performance of chrome-free Dacromet coatings. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the present invention provides a chrome-free Dacromet coating, which can increase the hardness of the chrome-free Dacromet coating.

[0006] In order to achieve the above-mentioned purpose of the invention, the technical solution adopted by the present invention is: a chromium-free Dacromet coating, including additives, and the additives include diazole substances and amine derivatives.

[0007] The beneficial effects of the present invention are as follows: the additive disclosed in the present invention is added to the chromium-free Dacromet coating, which can greatly improve the hardness of the coating without changing the original coating performance. Compared with the traditional chromium-containing Dacromet coating, the chromium-free Dacromet coating avoids the use of heavy metal chromium, thereby reducing the potential harm to the environment and human health. The additive of the present invention has the characteristics of environmental protection, non-toxicity, low dosage concentration, and low use cost, and is suitable for the surface protection of various materials such as steel, cast iron, aluminum and its alloys, and iron-based powder metallurgy.

[0008] As additives, oxadiazole substances and amine derivatives can form stable chemical bonds with the metal surface and provide a good anti-corrosion protective layer.

[0009] Furthermore, in the above-mentioned chromium-free Dacromet coating, the oxadiazole substance is 2-o-chlorophenyl-4,5-diphenylimidazole, and the amine derivative is N-(tert-butyloxycarbonyl)ethanolamine.

[0010] Furthermore, in the above-mentioned chromium-free Dacromet coating, the mass proportion of 2-o-chlorophenyl-4,5-diphenylimidazole in the additive is 30-50 g / L, and the mass proportion of N-(tert-butyloxycarbonyl)ethanolamine in the additive is 15-25 g / L.

[0011] Furthermore, in the above-mentioned chromium-free Dacromet coating, the mass ratio of 2-o-chlorophenyl-4,5-diphenylimidazole and N-(tert-butyloxycarbonyl)ethanolamine is 2:1.

[0012] Furthermore, in the above-mentioned chrome-free Dacromet coating, the concentration of 2-o-chlorophenyl-4,5-diphenylimidazole in the chrome-free Dacromet coating is 3-5 g / L; the concentration of N-(tert-butyloxycarbonyl)ethanolamine in the chrome-free Dacromet coating is 1.5-2.5 g / L.

[0013] Furthermore, the above-mentioned chrome-free Dacromet paint, the chrome-free Dacromet paint, calculated by mass concentration, contains the following components: zinc powder 208g / L, aluminum powder 52g / L, ethylene glycol 110g / L, OP-emulsifier 70g / L, sodium molybdate 60g / L, 1,1,5,5-tetramethyl-3,3-diphenyltrisiloxane 50g / L, hydroxyethyl cellulose 4g / L, isooctyl alcohol 1g / L, 2-o-chlorophenyl-4,5-diphenylimidazole 3-5g / L, N-(tert-butyloxycarbonyl)ethanolamine 1.5-2.5g / L, and deionized water as the balance.

[0014] Furthermore, the pH value of the chrome-free Dacromet coating is 5-7.

[0015] Furthermore, the above-mentioned chrome-free Dacromet coating has a specific gravity of 1.2kg / m3 to 1.4kg / m3.

[0016] Furthermore, the above-mentioned chrome-free Dacromet paint has a viscosity of 10Pa·s to 20Pa·s when sprayed; a viscosity of 40Pa·s to 60Pa·s when dipped; and a viscosity of 35Pa·s to 40Pa·s when brushed.

[0017] Furthermore, the chrome-free Dacromet coating has an operating temperature of 10 to 25°C.

[0018] Furthermore, the method for using the chrome-free Dacromet coating is two-coating and two-baking, comprising the following steps:

[0019] S1, first coating, first bake in the pre-baking zone, then bake in the high temperature zone; the pre-baking zone temperature is 100-120℃, the baking time is 10min; the high temperature zone temperature is 300-320℃, the baking time is 30min;

[0020] S2, the second coating, first baked in the pre-baking zone, and then heated to the high temperature zone for baking; the temperature in the pre-baking zone is 100-120°C, and the baking time is 10 minutes; the temperature in the high temperature zone is 300-320°C, and the baking time is 40 minutes.

[0021] The beneficial effects of the present invention are as follows: adding an additive to a chromium-free Dacromet coating can further improve the hardness of the coating without changing the original coating performance and the stability of the coating. The coating does not contain heavy metal chromium, and while improving the performance, it can replace the Dacromet coating and play a role in protecting the environment. The additive has the characteristics of being environmentally friendly, non-toxic, low in dosage concentration and low in cost, and is suitable for surface protection of various materials such as steel, cast iron, aluminum and its alloys, and iron-based powder metallurgy. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is the structural formula of 2-o-chlorophenyl-4,5-diphenylimidazole;

[0023] Figure 2 It is the structural formula of N-(tert-butyloxycarbonyl)ethanolamine. DETAILED DESCRIPTION

[0024] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.

[0025] Example 1

[0026] 1. The mass ratios of the various components of the additives in this example are as follows:

[0027] 2-o-chlorophenyl-4,5-diphenylimidazole 30g / L

[0028] N-(tert-Butyloxycarbonyl)ethanolamine 15g / L

[0029] 2. The preparation method of the additive in this embodiment is as follows:

[0030] (1) Preparation of N-(tert-butyloxycarbonyl)ethanolamine solution: 15 g of N-(tert-butyloxycarbonyl)ethanolamine was weighed on a balance and added to 500 mL of deionized water. The solution was stirred until uniformly mixed and set aside.

[0031] (2) Weighing 2-o-chlorophenyl-4,5-diphenylimidazole: Use a balance to weigh 30 g of 2-o-chlorophenyl-4,5-diphenylimidazole and set aside.

[0032] (3) Preparation of chromium-free Dacromet coating additives: Add the 2-o-chlorophenyl-4,5-diphenylimidazole weighed in step (2) to the N-(tert-butyloxycarbonyl)ethanolamine solution prepared in step (1), stir thoroughly to mix them completely, and finally make up to 1 L with deionized water, and continue stirring to mix the solution evenly.

[0033] 3. Performance testing

[0034] Prepare chromium-free Dacromet coating according to the following raw materials:

[0035]

[0036]

[0037] The process conditions used in this embodiment are:

[0038] pH value of coatings 5.2 Specific gravity of paint 1.22 Paint use temperature normal temperature How to use the paint Spraying

[0039] After the coating is prepared and matured, the chrome-free Dacromet coating is sprayed on the tinplate as the experimental test piece. The chrome-free Dacromet coating of the present invention adopts a two-coating and two-baking process. The first coating pre-baking zone temperature is 120±2℃, the baking time is 10min, the high temperature zone temperature is 320±5℃, and the baking time is 30min; the second baking temperature is the same as the first coating, and the high temperature baking time is 40min. After the drying is completed, take it out, cool it naturally, and dry it for 2 days.

[0040] The tinplate test piece was sprayed with the coating of the above ratio but without additives under the same conditions, and then dried and cooled to dry for 2 days. After the coating dried, the appearance of the above two coatings was observed, and the hardness of the coating was tested by pencil scratch hardness method.

[0041] 4. Test results

[0042] The chrome-free Dacromet coating with and without the additive of the present invention was applied, and both coatings were smooth and continuous, and the color was silvery white. After testing, the chrome-free Dacromet coating without the additive of the present invention did not change after a 2H pencil was pushed over the coating surface under the pencil scratch test method; after a 3H pencil was pushed over the coating surface, a scratch phenomenon appeared on the coating surface. For the chrome-free Dacromet coating with the additive of the present invention, the coating surface did not change after a 4H pencil was pushed over the coating surface under the pencil scratch test method. After a 5H pencil was pushed over the coating surface, there was a scratch phenomenon on the coating surface. According to experimental tests, the hardness of the coating of the chrome-free Dacromet coating with the additive of the present invention increased from 2H to 4H, and the hardness of the coating was significantly improved. The chrome-free Dacromet coating with the additive of the present invention has no obvious difference in appearance from the chrome-free Dacromet coating without the additive of the present invention, and can significantly increase the hardness of the coating while ensuring that the appearance and other properties of the coating remain unchanged.

[0043] Example 2

[0044] 1. The mass ratio of each component of the additive in this example is as follows:

[0045] 2-o-chlorophenyl-4,5-diphenylimidazole 40g / L

[0046] N-(tert-Butyloxycarbonyl)ethanolamine 20g / L

[0047] 2. The preparation method of the chromium-free Dacromet coating additive in this embodiment is the same as that in Embodiment 1, except that the mass ratios of the components are different.

[0048] 3. Performance testing

[0049] Prepare chromium-free Dacromet coating according to the following raw materials:

[0050] Zinc powder 208g / L Aluminum powder 52g / L Ethylene glycol 110g / L OP-emulsifier 70g / L Sodium molybdate 60g / L 1,1,5,5-Tetramethyl-3,3-diphenyltrisiloxane 50g / L Hydroxyethyl Cellulose 4g / L 2-Ethylhexyl alcohol 1g / L 2-O-chlorophenyl-4,5-diphenylimidazole 4g / L N-(tert-Butyloxycarbonyl)ethanolamine 2g / L Deionized water margin

[0051] The process conditions used in this embodiment are:

[0052] pH value of coatings 5.3 Specific gravity of paint 1.23 Paint use temperature normal temperature How to use the paint Spraying

[0053] After the coating is prepared and matured, the chrome-free Dacromet coating is sprayed on the tinplate as the experimental test piece. The chrome-free Dacromet coating of the present invention adopts a two-coating and two-baking process. The first coating pre-baking zone temperature is 120±2℃, the baking time is 10min, the high temperature zone temperature is 320±5℃, and the baking time is 30min; the second baking temperature is the same as the first coating, and the high temperature baking time is 40min. After the drying is completed, take it out, cool it naturally, and dry it for 2 days.

[0054] After the coating is dried, the appearance of the coating is observed, and the hardness of the coating is tested by a pencil scratch hardness method.

[0055] 4. Test results

[0056] The chrome-free Dacromet coating coated with the additive of the present invention has a smooth and continuous coating with a silvery white color. After testing, the chrome-free Dacromet coating with the additive of the present invention did not change after a 5H pencil was pushed over the coating surface under the pencil scratch test. After a 6H pencil was pushed over the coating surface, there was a scratch phenomenon on the coating surface. According to experimental tests, the hardness of the coating of the chrome-free Dacromet coating with the additive of the present invention increased from 2H to 5H, and the hardness of the coating was significantly improved. The chrome-free Dacromet coating with the additive of the present invention has no obvious difference in appearance from the chrome-free Dacromet coating without the additive of the present invention, and can significantly increase the hardness of the coating while ensuring that the appearance and other properties of the coating remain unchanged.

[0057] Example 3

[0058] 1. The mass ratio of each component of the additive in this example is as follows:

[0059] 2-o-chlorophenyl-4,5-diphenylimidazole 50g / L

[0060] N-(tert-Butyloxycarbonyl)ethanolamine 25g / L

[0061] 2. The preparation method of the chromium-free Dacromet coating additive in this embodiment is the same as that in Embodiment 1, except that the mass ratios of the components are different.

[0062] 3. Performance testing

[0063] Prepare chromium-free Dacromet coating according to the following raw materials:

[0064] Zinc powder 208g / L Aluminum powder 52g / L Ethylene glycol 110g / L OP-emulsifier 70g / L Sodium molybdate 60g / L 1,1,5,5-Tetramethyl-3,3-diphenyltrisiloxane 50g / L Hydroxyethyl Cellulose 4g / L 2-Ethylhexyl alcohol 1g / L 2-O-chlorophenyl-4,5-diphenylimidazole 5g / L N-(tert-Butyloxycarbonyl)ethanolamine 2.5g / L Deionized water margin

[0065] The process conditions used in this embodiment are:

[0066] pH value of coatings 5.6 Specific gravity of paint 1.24 Paint use temperature normal temperature How to use the paint Spraying

[0067] After the coating is prepared and matured, the chrome-free Dacromet coating is sprayed on the tinplate as the experimental test piece. The chrome-free Dacromet coating of the present invention adopts a two-coating and two-baking process. The first coating pre-baking zone temperature is 120±2℃, the baking time is 10min, the high temperature zone temperature is 320±5℃, and the baking time is 30min; the second baking temperature is the same as the first coating, and the high temperature baking time is 40min. After the drying is completed, take it out, cool it naturally, and dry it for 2 days.

[0068] After the coating is dried, the appearance of the coating is observed, and the hardness of the coating is tested by a pencil scratch hardness method.

[0069] 4. Test results

[0070] The chrome-free Dacromet coating coated with the additive of the present invention has a smooth and continuous coating with a silvery white color. After testing, the chrome-free Dacromet coating with the additive of the present invention did not change after a 4H pencil was pushed over the coating surface under the pencil scratch test. After a 5H pencil was pushed over the coating surface, there was a scratch phenomenon on the coating surface. According to experimental tests, the hardness of the coating of the chrome-free Dacromet coating with the additive of the present invention increased from 2H to 4H, and the hardness of the coating was significantly improved. The chrome-free Dacromet coating with the additive of the present invention has no obvious difference in appearance from the chrome-free Dacromet coating without the additive of the present invention, and can significantly increase the hardness of the coating while ensuring that the appearance and other properties of the coating remain unchanged.

[0071] Example 4

[0072] 1. The mass ratio of each component of the additive in this example is as follows:

[0073] 2-o-chlorophenyl-4,5-diphenylimidazole 44g / L

[0074] N-(tert-Butyloxycarbonyl)ethanolamine 22g / L

[0075] 2. The preparation method of the chromium-free Dacromet coating additive in this embodiment is the same as that in Embodiment 1, except that the mass ratios of the components are different.

[0076] 3. Performance testing

[0077] Prepare chromium-free Dacromet coating according to the following raw materials:

[0078]

[0079]

[0080] The process conditions used in this embodiment are:

[0081] pH value of coatings 5.4 Specific gravity of paint 1.23 Paint use temperature normal temperature How to use the paint Spraying

[0082] After the coating is prepared and matured, the chrome-free Dacromet coating is sprayed on the tinplate as the experimental test piece. The chrome-free Dacromet coating of the present invention adopts a two-coating and two-baking process. The first coating pre-baking zone temperature is 120±2℃, the baking time is 10min, the high temperature zone temperature is 320±5℃, and the baking time is 30min; the second baking temperature is the same as the first coating, and the high temperature baking time is 40min. After the drying is completed, take it out, cool it naturally, and dry it for 2 days.

[0083] After the coating is dried, the appearance of the coating is observed, and the hardness of the coating is tested by a pencil scratch hardness method.

[0084] 4. Test results

[0085] The chrome-free Dacromet coating coated with the additive of the present invention has a smooth and continuous coating with a silvery white color. After testing, the chrome-free Dacromet coating with the additive of the present invention did not change after a 4H pencil was pushed over the coating surface under the pencil scratch test. After a 5H pencil was pushed over the coating surface, there was a scratch phenomenon on the coating surface. According to experimental tests, the hardness of the coating of the chrome-free Dacromet coating with the additive of the present invention increased from 2H to 4H, and the hardness of the coating was significantly improved. The chrome-free Dacromet coating with the additive of the present invention has no obvious difference in appearance from the chrome-free Dacromet coating without the additive of the present invention, and can significantly increase the hardness of the coating while ensuring that the appearance and other properties of the coating remain unchanged.

[0086] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.

Claims

1. A chromium-free Dacromet coating, characterized in that: The invention comprises additives, wherein the additives include diazole substances and amine derivatives.

2. The chromium-free Dacromet coating according to claim 1, characterized in that: The diazole substance is 2-o-chlorophenyl-4,5-diphenylimidazole, and the amine derivative is N-(tert-butyloxycarbonyl)ethanolamine.

3. The chromium-free Dacromet coating according to claim 2, characterized in that: The mass proportion of 2-o-chlorophenyl-4,5-diphenylimidazole in the additive is 30-50 g / L, and the mass proportion of N-(tert-butyloxycarbonyl)ethanolamine in the additive is 15-25 g / L.

4. The chromium-free Dacromet coating according to claim 3, characterized in that: The mass ratio of 2-o-chlorophenyl-4,5-diphenylimidazole to N-(tert-butyloxycarbonyl)ethanolamine is 2:

1.

5. The chromium-free Dacromet coating according to claim 2-4, characterized in that: The use concentration of the 2-o-chlorophenyl-4,5-diphenylimidazole in the chrome-free Dacromet coating is 3-5 g / L; the use concentration of the N-(tert-butyloxycarbonyl)ethanolamine in the chrome-free Dacromet coating is 1.5-2.5 g / L.

6. The chromium-free Dacromet coating according to claim 5, characterized in that: The chromium-free Dacromet coating comprises the following components, calculated by mass concentration: 208 g / L zinc powder, 52 g / L aluminum powder, 110 g / L ethylene glycol, 70 g / L OP-emulsifier, 60 g / L sodium molybdate, 50 g / L 1,1,5,5-tetramethyl-3,3-diphenyltrisiloxane, 4 g / L hydroxyethyl cellulose, 1 g / L isooctyl alcohol, 3-5 g / L 2-o-chlorophenyl-4,5-diphenylimidazole, 1.5-2.5 g / L N-(tert-butyloxycarbonyl)ethanolamine, and the balance deionized water.

7. The chromium-free Dacromet coating according to claim 6, characterized in that: The pH value of the chromium-free Dacromet coating is 5-7.

8. The chromium-free Dacromet coating according to claim 7, characterized in that: The specific gravity of the chromium-free Dacromet coating is 1.2kg / m3 to 1.4kg / m3.

9. The chromium-free Dacromet coating according to claim 7, characterized in that: The viscosity of the chrome-free Dacromet coating when sprayed is 10Pa·s to 20Pa·s; the viscosity of the chrome-free Dacromet coating when dipped is 40Pa·s to 60Pa·s; the viscosity of the chrome-free Dacromet coating when brushed is 35Pa·s to 40Pa·s.

10. A method for using the chromium-free Dacromet coating according to any one of claims 1 to 9, characterized in that: The method of use is two coatings and two bakings, comprising the following steps: S1, first coating, first baking in the pre-baking zone, then baking in the high temperature zone; the pre-baking zone temperature is 100-120°C, the baking time is 10 minutes; the high temperature zone temperature is 300-320°C, the baking time is 30 minutes; S2, the second coating, first baking in the pre-baking zone, and then baking in the high temperature zone; the temperature of the pre-baking zone is 100-120°C, and the baking time is 10 minutes; the temperature of the high temperature zone is 300-320°C, and the baking time is 40 minutes.